Importance of epigenetics in animal breeding - Zeric, Dijana (2012)
ABSTRACT The aim of this study was to give an overview of the evidence for genomic imprinting in livestock and other mammals as well as outline the potential use of gene imprinting in livestock breeding. Epigenetics is the mitotical and meiotical partial hereditary variation in genomic activity without any alterations of the DNA sequence. An example of epigenetic regulation is genomic imprinting where one allele’s expression differs depending on which parent it was inherited from. These parent-of-origin effects are currently overlooked in livestock production. Many economically important traits in livestock are so called quantitative traits, some of which have shown indication of being partially controlled by imprinted genes. A variety of imprinted genes have been found in livestock that affect traits such as milk yield, growth and carcass traits, fat and meat deposition and fetal development. The implementation of breeding programs taking imprinting into account, will require changes in the current standard breeding programs. More focus on the maternal contribution will be needed. It will also provide different breeding values for males and females, dominance deviations and additive genetic variances.